Towards an Understanding of Neighborhood and Individual Level Barriers to Lifestyle Change in Hamilton, Ontario - Jama, Sophie (My University, 2004)
The population health perspective, or the determinants of health approach, is an integral part of health research and policy in Canada and elsewhere. Determinants of health have typically been measured at the national and provincial levels. There is however, a growing interest in the relationship between local environments and health, therefore emphasizing the important role place has in influencing the health of populations or individuals. In addition, there is agreement that chronic diseases can be reduced through healthier lifestyle behaviors. Despite this knowledge, studies suggest that many Canadians do not reap the benefits of a healthy lifestyle. The objectives of this research are threefold: firstly, to explore individuals' perception of neighborhood; secondly, to document perceived meanings of health; and thirdly, to investigate (individual and neighborhood level) facilitators and barriers to healthy lifestyle. This research uses a parallel case study design and a qualitative approach to investigate four different neighborhoods in Hamilton, Ontario (the Mountain, Aberdeen, Downtown core, and Industrial area). Results from qualitative interviews (n=lO per neighborhood) indicate that the Downtown and Industrial areas have more neighborhood level barriers to healthy lifestyle change, such as lack of amenities and pollution. The Aberdeen and Mountain neighborhoods have more individual level barriers, such as lack of motivation and time. The key findings of this study corroborate existing literature that both characteristics of individuals and of neighborhoods can influence lifestyle behaviors. The results can therefore be used to inform public health policy and enhance our understanding of the determinants of health at the local level.
Keywords: Geography; Geography